Urgensi Manajemen Humas Dalam Peningkatkan Mutu Pendidikan di Madrasah - Bahrudin, Ahmad Robeth (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Madrasa today are different from madrasas five years ago. Madrasahs are still often given second place and marginalized by some groups in terms of the quality of education. Madrasahs are considered unable to involve the community in preparing their children to face life following the progress of the times. In fact, society has a very strong influence on whether an educational institution advances or not. The purpose of this research is to determine the importance of community relations that are formed or function in a madrasa. The community or parents and local residents can participate actively and function optimally and can become accurate informants about the development and progress of a madrasa. Awareness of improving quality in a madrasa can reduce public misunderstandings about everything that develops in a madrasa. Community criticism and suggestions can become an evaluation and reflection for the progress of a madrasa. The method in this research uses a literature review approach. The results of the research obtained are that the creation of success in improving the quality of education in a madrasah can be a benchmark for a madrasah in terms of (1) as a form of responsibility of the madrasah to the community, (2) as a forum to equip the community to care and be wise in choosing education for their children. their children and (3) the success of the madrasah in establishing good relationships and cooperation with the community, so that the existence of the madrasah is accepted in its environment